DETECTION OF ANAPLASMA INFECTION IN ASYMTOMATIC COWS - I Putu Gede Yudhi Arjentinia; Bamphen Keomoungkhoun; Somboon Sangmaneedet; Chaiyapas Thomrongyoswittayakul; Weerapol Taweenan (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
The diagnosis of Anaplasma is typically carried out through morphological identification based on the presence of inclusion bodies located at the margins of erythrocytes. Microscopic examination of blood smears stained with Wright’s–Giemsa is generally suitable for detecting acute anaplasmosis in clinically suspected animals. This study aimed to compare the diagnostic accuracy of microscopic examination and conventional polymerase chain reaction (PCR) for detecting A. marginale in asymptomatic (carrier) cattle. A total of 385 blood samples were collected from cows without clinical symptoms. The sensitivity and specificity of microscopic detection were evaluated against conventional PCR results. The sensitivity and specificity of microscopic results were compared with A. marginale by conventional PCR. The results revealed 3.40% and 12.73% positive animals by microscopy and conventional PCR with significant differences (P=0.03). The value of Kappa between microscopic examination and conventional PCR has indicated a fair level of agreement (0.32). Microscopic examination showed 6.10% sensitivity and 97.40% specificity compared to conventional PCR's 100% sensitivity and specificity. These results indicate that conventional PCR is a more accurate and reliable method for detecting A. marginale in asymptomatic cattle. The limitations of microscopy, particularly in carrier animals, include the very low number of infected erythrocytes, difficulty in identifying well-stained Anaplasma organisms, and challenges in distinguishing A. marginale from A. centrale.